Posisi Geopolitik Yordania dan Dukungannya terhadap Palestina - Amalia, Zahra; Ardiyanti, Dwi; Mubarok, Sofi (Jurnal ICMES, 2025)
This study aims to analyze how the geopolitical dynamics of the Hashemite Kingdom of Jordan influenced its support for Palestine in the context of the Israeli–Palestinian conflict. Using a geopolitical approach, this study examines Jordanian–Palestinian relations before and after the normalization of Jordanian-Israeli relations in 1994, as well as Jordan's response to changes in the regional political landscape, including post-Abraham Accords. This study uses a qualitative method based on literature analysis to examine the political, economic, and strategic factors that shape Jordan's foreign policy. The results show that Jordan's strategic geographical position, limited resources, and historical role as the custodian of Jerusalem's holy sites greatly influenced the direction of its policy. Although Jordan has established pragmatic cooperation with Israel for stability and economic interests, the country maintains diplomatic support for the Palestinians, especially regarding the issue of Jerusalem and the rights of the Palestinian people. The study concludes that regional geopolitics significantly shape and limit Jordan's foreign policy space.